بول ريكور قارئا لشخصانية إيمانويل مونيي - مجيديلة، إبراهيم (المركز العربي للأبحاث ودراسة السياسات, 2018)
إن تاريخ الفلسفة مثل نهر هيراقليطس دائم الجريان، تتغير مياهه باستمرار، وفي ذلك دلالة على حيوية الفلسفة وفاعليتها والتزامها بقضايا عصرها. والشخصانية جزء من هذا التاريخ، انبثقت ردة فعل على الأزمة الروحية والسياسية التي ألمت بالمجتمعات الأوروبية، ومست الإنسان في كينونته وحضوره في العالم. ومنذ نشأتها ثم تطورها فيما بعد من خلال أعمال إيمانويل مونيي، أصبحت الشخصانية موضوع قراءات مختلفة ومراجعات مستمرة قام بها عديد الفلاسفة. ويعد بول ريكور من أوائل الذين اعتنوا بالتراث الشخصاني نقدا وتأويلا من أجل الكشف عن طبيعته وأصوله ومقاصده.
The history of philosophy meanders like Heraclitus’ river, moving with the ever-changing flow. In this flexibility lies the vitality, effectiveness and contemporary relevance of philosophy Personalism is one piece of this history. This school of thought emerged as a reaction to the spiritual and political crisis that was unfolding in European societies, and affecting the human being’s existence and presence in the world. Since its inception and subsequent development through the works of Emmanuel Mounier, Personalism has been the subject of various readings and ongoing reviews by many philosophers. Paul Ricoeur is one of the first intellectuals to take on the legacy of Personalism with a critique and an interpretation that reveals its nature, origins and purposes.
Keywords: ريكور، بول ، ت. 2005 م. -- مونيي، إيمانويل، ت. 1804 م. -- النزعة الإنسانية